Effect of Applying a Rehabilitation Program on Knee Joint Function after Traumatic Injuries - حلاج فاطمة; جوني أحمد; نجار وائل (Latakia University Journal -Medical Sciences Series, 2020)
During the past two decades, the importance of treating knee joint injuries and reducing complications has increased. Also, attention has been given to the treatment programs that help to Hospitalization in the shortest possible time due to the increase in the prevalence of these injuries as a result of injuries caused by accidents and violent sports Objective: Assess the effect of applying a rehabilitation program on knee joint function after traumatic injuries Setting: This study was carried out in the Division of Orthopedic Surgery and Physical Therapy Division Subjects: The sample comprised 40 patients chosen randomly from the two gender who have traumatic knee injuries (n=20 in each group). The control group received the hospital therapies. The experimental received a rehabilitation program and this program was administered for 56 mints once a day three times in the first week and two times in the second week. All patients were assessed by using Knee Outcome Survey (Activities of Daily Living Scale) after two weeks of implementing the sessions. Result: the knee joint function improved in the experimental group compared to the control group. This improvement is due to the implementation of the rehabilitation program. Conclusion: The rehabilitation program succeeded in improving knee joint function. Recommendations: Send the results of this research to all hospitals and rehabilitation centers in the province to benefit from them